Electrophysiology of subject-verb agreement mediated by speakers’ gender - Hanulíková, Adriana; Carreiras, Manuel (Frontiers in Psychology, 2015)
An important property of speech is that it explicitly conveys features of a speaker's identity such as age or gender. This event-related potential (ERP) study examined the effects of social information provided by a speaker’s gender, i.e. the conceptual representation of gender, on subject-verb agreement. Despite numerous studies on agreement, little is known about syntactic computations generated by speaker characteristics extracted from the acoustic signal. Slovak is well suited to investigate this issue because it is a morphologically rich language in which agreement involves features for number, case, and gender. Grammaticality of a sentence can be evaluated by checking a speaker’s gender as conveyed by his/her voice. We examined how conceptual information about speaker gender, which is not syntactic but rather social and pragmatic in nature, is interpreted for the computation of agreement patterns. ERP responses to verbs disagreeing with the speaker's gender (e.g., a sentence including a masculine verbal inflection spoken by a female person 'the neighbours were upset because I *stoleMASC plums’) elicited a larger early posterior negativity compared to correct sentences. When the agreement was purely syntactic and did not depend on the speaker’s gender, a disagreement between a formally-marked subject and the verb inflection (e.g., the womanFEM *stoleMASC plums) resulted in a larger P600 preceded by a larger anterior negativity compared to the control sentences. This result is in line with proposals according to which the recruitment of non-syntactic information such as the gender of the speaker results in N400-like effects, while formally-marked syntactic features lead to structural integration as reflected in a LAN/P600 complex.